Simulated Order Verification and Medication Reconciliation during an Introductory Pharmacy Practice Experience - Metzger, Nicole L. (Am J Pharm Educ, 2015)
Objective. To create, implement, and assess a simulated medication reconciliation and an order verification activity using hospital training software. Design. A simulated patient with medication orders and home medications was built into existing hospital training software. Students in an institutional introductory pharmacy practice experience (IPPE) reconciled the patient’s medications and determined whether or not to verify the inpatient orders based on his medical history and laboratory data. After reconciliation, students identified medication discrepancies and documented their rationale for rejecting inpatient orders. Assessment. For a 3-year period, the majority of students agreed the simulation enhanced their learning, taught valuable clinical decision-making skills, integrated material from previous courses, and stimulated their interest in institutional pharmacy. Overall feedback from student evaluations about the IPPE also was favorable. Conclusion. Use of existing hospital training software can affordably simulate the pharmacist’s role in order verification and medication reconciliation, as well as improve clinical decision-making.